Plankton Community Metabolism in Western Australia: Estuarine, Coastal and Oceanic Surface Waters - Garcia-Corral, Lara S.; Duarte, Carlos M.; Agusti, Susana (Frontiers in Marine Science, 2021)
Net community production (NCP) is a community level process informing on the balance between production and consumption, determining the role of plankton communities in carbon and nutrient balances fuelling the marine food web. An assessment of net and gross community production (NCP, GPP) and community respiration (CR) in 86 surface plankton communities sampled between 15º and 36º South along coastal Western Australia (WA) revealed a prevalence of net autotrophic metabolism (GPP/CR > 1), comprising 81% of the communities sampled. NCP, GPP, and CR decreased with decreasing nutrient and chlorophyll-a concentrations, from estuarine, to coastal and oceanic waters. CR, standardized per unit chlorophyll-a, increased with temperature, with higher activation energies (Ea) than GPP per unit chlorophyll-a (Ea 1.07 ± 0.18 eV and 0.65 ± 0.15 eV, respectively) either across ecosystem types and for coastal and estuary communities alone, indicating plankton CR to increase much faster with warming than GPP. These results characterize surface plankton communities across Western Australia as CO2 sinks, the stronger thermal-dependence of respiration that gross primary production rates suggests that their role may weaken with future warming.